PENGARUH BAHAN KEMASAN DAN LAMA INKUBASI TERHADAP KUALITAS TEMPE KACANG GUDE SEBAGAI SUMBER BELAJAR IPA - Sayuti, Sayuti (UNIVERSITAS MUHAMMADIYAH METRO, 2015)
Pigeon pea can be used as an alternative of soybeans that contain protein, fats, and carbohydrates. Objective: (1) determine the effect of various packaging on the quality of pigeon pea tempe, (2) the effect of long incubation on the quality of pigeon pea tempe, (3) the interaction of various packaging and long incubation on the quality of pigeon pea tempeh. (4) design the research results as a science learning resource for 9th grade junior high school on the topic of biotechnology. The research design used completely randomized design. Research conducted at the Laboratory of Food Products Technology in Polinela in May 11th until 25th, 2015. Data were analyzed using SPSS 16.0, the data proximate using Univariate and Tukey, the data organoleptic using Friedman test. From the results of the proximate analysis turns out there is influence between the packaging materials and the long incubation of the tempe quality. Protein content increased, while fat and carbohydrates decreases with increasing time of incubation. Organoleptic analysis of the soybean leaves are packed with incubation time 36 and 42 hours is preferred by the panelists than plastic packaging with an incubation time of 48 hours. The results of the research can be used to design learning resources of scince for junior high School, based LKPD Form based scientific approach.Kata Kunci: Bahan kemasan, lama inkubasi, kacang gude, kualitas tempe, sumber belajar